Breast metastasis of cervical cancer: A case report and systematic literature review - Jian-yong, Zhang; Guang-ping, Zeng; Xue, Wang; Shi-min, Zhang; Zhen-guo, Zhao (Frontiers in Oncology, 2022)
It has been reported that extramammary malignant tumors metastasize to the breast, but cervical cancer metastasis to the breast is very rare. At present, there are only dozens of reports about cervical cancer metastasis to breast in the world. It is difficult to distinguish between primary breast cancer(PBC) and metastatic breast cancer(MBC). We report a 44-year-old woman who underwent surgery, chemotherapy and radiotherapy for cervical cancer five years ago. Then she was hospitalized for finding a left breast mass measured 2.9 cm × 2.7 cm in chest CT. Pathological examination combined with immunohistochemical staining showed that the mass came from the cervix. Then the patient received systematic chemotherapy and interstitial brachytherapy(IB) for the breast mass and got a great result. Cervical cancer rarely metastasize to the breast. In this case, we confirmed the diagnosis of breast mass by histopathological examination and immunohistochemical. IB achieved a good result in the treatment of the breast mass. We hope to provide reference of prognosis and treatment when facing this situation by presenting this case.